Impact of Holocene climate change on silicon cycling in Lake 850, Northern Sweden. (October 2021) - Zahajská, Petra; Cartier, Rosine; Fritz, Sherilyn C; Stadmark, Johanna; Opfergelt, Sophie; Yam, Ruth; Shemesh, Aldo; Conley, Daniel J
Diatom-rich sediment in a small subarctic lake (Lake 850) was investigated in a 9400 cal. yr BP sediment record in order to explore the impact of Holocene climate evolution on silicon cycling. Diatom stable silicon isotopes (δ 30 Si BSi ) and biogenic silica (BSi) indicate that high BSi concentrations in sediment throughout the Holocene are associated with a lighter Si isotope source of dissolved silica (DSi), such as groundwater or freshly weathered primary minerals. Furthermore, higher BSi concentrations were favoured during the mid-Holocene by low detrital inputs and possibly a longer ice-free period allowing for more diatom production to occur. The diatomδ 30 Si BSi signature shows a link to changes in regional climate and is influenced by length of diatom growth period and hydrological fluctuations. Lighter Si isotopic values occur during the mid-Holocene, when climate is inferred to be more continental and drier, with pronounced seasonality. In contrast, a heavier Si isotopic signature is observed in the early and late Holocene, when oceanic influences are thought to be stronger and the climate wetter. Theδ 30 Si BSi values have generally lighter signatures as compared with other studies, which supports a light DSi source.